B-Boy Alien Ness visited campus to teach students the art of "breaking" at the Jackson Gym Monday. Photo 211 - Ko, Melody (Tufts Archival Research Center, 2008)
B-Boy Alien Ness visited campus to teach students the art of "breaking" at the Jackson Gym Monday. Alien Ness, who is also known as Luis Martinez, is legendary among b-boys and has performed with many breakdancing crews, including the New York City Breakers and the Rock Steady Crew.